Внесок відділу дендрології та паркознавства у вивчення дендрофлори України і поліпшення довкілля - Kohno, M.A.; Kuznetsov, S.I.; Levon, F.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
Main scientific achievements of the Department of Dendrology and Parklearning at the period of the existence of M.M. Gryshko National Botanical Gardens are reflected.